The Impact of Bullying on Students Social Development at SMA Negeri 11 Makassar - Sintawati, Sintawati; Najamuddin, Najamuddin; Alwi, Alimin (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
The problem in this study is the rampant cases of bullying in the environment of SMA Negeri 11 Makassar which have a negative impact on the development of students' social skills, both as victims, perpetrators, and recipients of sanctions for bullying. This study aims to analyze how student characteristics affect the ability to interact socially in the school environment. The method used is a qualitative approach with a case study type, using in-depth interview and observation techniques. The research sample consisted of students identified as victims of bullying, perpetrators of bullying, and students who received sanctions for bullying. The results showed that victims tended to experience decreased self-confidence and withdraw from the social environment, while perpetrators showed dominant manipulative behavior. On the other hand, students who received sanctions in the form of counseling showed increased social awareness and more positive behavioral changes than those who only received administrative punishment. The implications of the results indicate that handling bullying cases requires a more educational and empathetic approach, not just punishment. As a result, schools can create a learning environment that is more inclusive, safe, and supports the development of students' character and social skills as a whole.